EVALUATION OF GENETIC DIVERSITY IN CACAO COLLECTED FROM KOLAKA, SOUTHEAST SULAWESI, USING SSR MARKERS - Rubiyo Rubiyo; Nur Kholilatul Izzah; Indah Sulistiyorini; Cici Tresniawati (Indonesian Agency for Agricultural Research and Development, 2015)
Kolaka, which is located in Southeast Sulawesi, has long been known as one of cacao production centers in Indonesia. Therefore, many different cacao germplasms can be found in this region. The study aimed to evaluate genetic diversity and relationships of 12 cacao genotypes collected from Kolaka. Genomic DNA was extracted by using a modified CTAB method. Meanwhile, genetic diversity was analyzed based on 16 SSR markers, which then separated by 6% non-denaturing polyacryl-amide gel electrophoresis. The result showed that all of those markers, 14 markers exhibited polymorphism and subsequently used for data analysis using NTSYS and PowerMarker program. About 70 different alleles were generated from 12 cacao genotypes analyzed with an average of 5 alleles per locus. Average value of polymorphism information content (PIC) resulted in this study was 0.59. The cluster analysis using UPGMA method based on the genetic similarity coefficient revealed that all cacao genotypes were separated into three major groups. The first group consisted of five cacao genotypes, the second one held four cacao genotypes, whereas the third group contained three genotypes. This result indicates that three genotypes that clustered separately from the others could be used as a good clonal candidate for cacao breeding program. The information resulted from this present study would be useful for future cacao breeding program, especially in efforts to release a new variety.